Medicolegal Aspects of Visum Et Repertum in Sexual Violence Criminal Cases - Renny Sumino; Adriano; Budi Pramono (JILPR Journal Indonesia Law and Policy Review, 2023)
One important component in disclosing the cases of criminal acts of sexual violence case is Visum et Repertum (VeR). Based on article 133 of the Criminal Procedure Code. VeR clarifies cases, especially in the context of proving someone's guilt relating to the body or parts of the human body. The purpose of this research is to analyze the medicolegal aspect in handling TPKS victims, especially victims of rape or sexual intercourse. By using normative research methods and using statutory and conceptual approaches. TPKS arrangements are regulated in Law Number 12 of 2022 concerning Crimes of Sexual Violence. Handling of TPKS victims is regulated through Minister of Health Decree number 1226/Menkes/SK/XII/2009 concerning Guidelines for the Management of Integrated Services for Victims of Violence Against Women and Children in Hospitals. Indonesian medical council regulation number 66 of 2021 concerning forensic and medicolegal medical education standards regulates clinical authority in handling TPKS victims. There are two regulations related to medical services for legal purposes, Minister of Health Regulation Number 38 of 2022 concerning Medical Services for Legal Purposes and Minister of Health Regulation Number 77 of 2015 concerning Guidelines for Mental Health Examination for the Interests of Law Enforcement.